Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1242/dev.00284
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of theC. eleganszygote proceeds via distinct establishment and maintenance phases

Abstract: Polarization of the C. elegans zygote along the anteriorposterior axis depends on cortically enriched (PAR) and cytoplasmic (MEX-5/6) proteins, which function together to localize determinants (e.g. PIE-1) in response to a polarizing cue associated with the sperm asters. Using timelapse microscopy and GFP fusions, we have analyzed the localization dynamics of PAR-2, PAR-6, MEX-5, MEX-6 and PIE-1 in wild-type and mutant embryos. These studies reveal that polarization involves two genetically and temporally dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

39
469
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(511 citation statements)
references
References 34 publications
39
469
1
2
Order By: Relevance
“…The independence of NR on RhoA activity is not entirely surprising as recent work links the Cdc42/Par6/PKC complex to the regulated degradation of RhoA during dynamic movements of the plasma membrane (Wang et al, 2003); moreover, MT polarization has previously been shown to be independent of Rho-dependent contractility in other mammalian cells (Omelchenko et al, 2002). The role of Cdc42 in controlling MTOC positioning in Swiss 3T3 fibroblasts concurs with results previously obtained in the nematode C. elegans (Cuenca et al, 2003), astrocytes (Etienne-Manneville andHall, 2001, 2003), and bovine aortic endothelial cells (BAEC; Tzima et al, 2003). Our results, however, seemingly conflict with those obtained by Wojciak-Stothard and Ridley (2003), who showed that MTOC polarization in human umbilical vein endothelial cells (HUVEC) is mediated by Rho and Rac, not Cdc42.…”
Section: Mtoc Repositioning and Nucleus Movement Are Mediated By Cdc42supporting
confidence: 84%
“…The independence of NR on RhoA activity is not entirely surprising as recent work links the Cdc42/Par6/PKC complex to the regulated degradation of RhoA during dynamic movements of the plasma membrane (Wang et al, 2003); moreover, MT polarization has previously been shown to be independent of Rho-dependent contractility in other mammalian cells (Omelchenko et al, 2002). The role of Cdc42 in controlling MTOC positioning in Swiss 3T3 fibroblasts concurs with results previously obtained in the nematode C. elegans (Cuenca et al, 2003), astrocytes (Etienne-Manneville andHall, 2001, 2003), and bovine aortic endothelial cells (BAEC; Tzima et al, 2003). Our results, however, seemingly conflict with those obtained by Wojciak-Stothard and Ridley (2003), who showed that MTOC polarization in human umbilical vein endothelial cells (HUVEC) is mediated by Rho and Rac, not Cdc42.…”
Section: Mtoc Repositioning and Nucleus Movement Are Mediated By Cdc42supporting
confidence: 84%
“…PAR-3 and PAR-6 localize to the anterior cortex in wild-type embryos (Etemad-Moghadam et al 1995;Hung and Kemphues 1999). In par-2 mutants, polarity cannot be maintained and the anterior PARs expand toward the posterior (Cuenca et al 2003). We observed that PAR-3 and PAR-6 proteins are restricted to the anterior cortex of most nos-3(q650); par-2(it5ts) double-mutant embryos (Figure 2).…”
Section: Rnai Clone Genementioning
confidence: 76%
“…The first division of the embryo is asymmetric, resulting in two cells that are different in size and fate. The seven PAR proteins (PAR-1 to PAR-6 and PKC-3) are found at the cortex of the zygote and are responsible for specifying the anteroposterior axis of polarity (Kemphues and Strome 1997;Tabuse et al 1998;Cuenca et al 2003). Embryos mutant for any par gene do not properly establish polarity, undergo symmetric cell divisions, and fail to hatch.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ainsi dans un mutant par-2, le complexe antérieur peut s'étendre jusqu'au pôle postérieur et occuper uniformément le cortex ( Figure 1B). Inversement, dans un mutant par-6, le domaine PAR-2 demeure uniforme sur l'intégralité du cortex [6]. Chaque protéine PAR est …”
Section: Découverte Des Protéines Par Dans L'embryon De C Elegansunclassified